University Funding Reform, Competition and Teaching Quality - Alexander Kemnitz (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
This paper explores the impact of university funding reform on teaching quality competition. It shows that a graduate tax with differentiated, but state-regulated fees maximises the higher education surplus, whereas student grants as well as pure and income contingent loans do not. Fee autonomy for universities leads to results inferior to properly state controlled fees and can make the majority of students even worse off than a central student assignment system with very poor teaching incentives.
Keywords: I22; L13; H52; 330; Higher Education; University Competition; Tuition Fees; Hochschulfinanzierung; Studienfinanzierung; Reform; Wettbewerb; Studium; Dienstleistungsqualität; Theorie